On Concircular 𝜙-Recurrent 𝐾-Contact Manifold Admitting Semisymmetric Metric Connection - Venkatesha; K. T. Pradeep Kumar; C. S. Bagewadi; Gurupadavva Ingalahalli (International Journal of Mathematics and Mathematical Sciences)
In the present paper, we have studied 𝜙-recurrent and concircular 𝜙-recurrent 𝐾-contact manifold with respect to semisymmetric metric connection and obtained some interesting results.